Assessment of Pharmacokinetic Interaction Between Letermovir and Fluconazole in Healthy Participants. Issue 2 (22nd July 2020) - Adedoyin, Adedayo; Fancourt, Craig; Menzel, Karsten; Zhao, Tian; Tomek, Charles; Panebianco, Deborah; McCrea, Jacqueline B.; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: Letermovir is a prophylactic agent for cytomegalovirus infection and disease in adult cytomegalovirus‐seropositive recipients of allogeneic hematopoietic stem cell transplant. As the antifungal agent fluconazole is administered frequently in transplant recipients, a drug–drug interaction study was conducted between oral letermovir and oral fluconazole. A phase 1 open‐label, fixed‐sequence study was performed in healthy females (N = 14, 19‐55 years). In Period 1, a single dose of fluconazole 400 mg was administered. Following a 14‐day washout, a single dose of letermovir 480 mg was administered (Period 2), and after a 7‐day washout, single doses of fluconazole 400 mg and letermovir 480 mg were coadministered in Period 3. Pharmacokinetics and safety were evaluated. The pharmacokinetics of fluconazole and letermovir were not meaningfully changed following coadministration. Fluconazole geometric mean ratio (GMR; 90% confidence interval [CI]) with letermovir for area under the concentration‐versus‐time curve from time 0 to infinity (AUC0‐∞ ) was 1.03 (0.99‐1.08); maximum concentration (Cmax ) was 0.95 (0.92‐0.99). Letermovir AUC0‐∞ GMR (90%CI) was 1.11 (1.01‐1.23), and Cmax was 1.06 (0.93‐1.21) following coadministration with fluconazole. Coadministration of fluconazole and letermovir was generally well tolerated.